Adequação de testes para avaliação da viabilidade e vigor de sementes de Cariniana estrellensis (Raddi) Kuntze - Kopper, Ana Caroline (2008)
The importance of native forest seeds analysis grew in recent years, due to economic and conservationist impulse that led to the increase of reforestation. Methodologies of tests to assess the quality of seed lots of this kind were little studied. The objective of this work was to establish bases for conducting tests of germination, tetrazolium and electrical conductivity with Cariniana estrellensis (Raddi) Kuntze seeds. For the germination test were used two types of substrate (sand and paper) and temperature (25°C and 20-30°C). In the tetrazolium test were evaluated concentrations 0,05%, 0,1% and 0,25% of the tetrazolium solution, in times of colour 2, 3, 4 or 5 hours. The electrical conductivity test consisted in employment of 2 g and 4 g of seeds to 50 mL and 75 mL of water. In all tests the design adopted was a completely randomized in a factorial 2 x 2 x 3 (two substrates, two temperatures and three lots) for the germination test, 2 x 12 (two lots and 12 periods of soaking) to the electrical conductivity test and 3 x 4 x 3 (three concentrations of the tetrazolium solution, 4 times of color and three lots) for the tetrazolium test. The substrate role and temperature of 25°C were more appropriate for the germination test. For the electrical conductivity test use of 2 g of seeds in 50 mL of water to soak for 48 hours was efficient in the classification of the lots on the vigor. The tetrazolium test presented several favourable results, thus the discretion of the analyst to choose the method most appropriate to your needs. Concentrations of 0,05% by 4 or 5 hours, 0,1% for 3 or 4 hours and 0,25% for 2 or 3 hours allowed the viability assessment, with results similar to germination test